Poligami dalam Masa ‘Iddah - Muzayyanah (Al-Adillah: Jurnal Hukum Islam, 2021)
Marriage is a human nature because all humans will experience it. In fact, marriage is the sunnah of the Prophet Muhammad SAW. Of course, the marriage that is the hope is one that can realize the goal of marriage to achieve a sakinah family, mawaddah wa rahmah as aspired in the Koran. But in fact, the implementation of marriage sometimes leads to divorce due to several factors, among them the factor of insufficient fulfillment of needs and some caused by cases of polygamy. . However, it cannot be denied that polygamy is a part justified by the original Sharia in accordance with the provisions taught by the Prophet Muhammad and the laws in the context of the Indonesian State. However, the problem is polygamy when the wife is in the iddah period. This is due to the technical instructions from the Director General of Bodybuilding No. DIV / Ed / 17/1979 concerning the Problem of Polygamy in Iddah. To see how the marriage is carried out according to legislation. be one of the reasons for this study